The calculated attenuated total reflection (ATR) for analyzing surface plasmon polaritons - Gunawan, Vincensius (International Journal of Scientific Research and Management (IJSRM), 2022)
The electromagnetic waves propagate in the interface between metal and dielectric can be simply called surface plasmon polariton. The surface plasmon polaritons were produced by the coupling of  incoming electromagnetic waves and collective vibrations of free charges on metal surface.  The generation of surface polaritons may be done using attenuated total reflection (ATR) method which was based on total internal reflection.  The method can be performed numerically by analyzing reflections on each involved interfaces.  The generated surface plasmon polaritons were represented by the appearance of the dip in the ATR spectroscopy.  In this paper, we presented the ATR spectroscopy for surface plasmon polaritons generated on gold-castor oil interface.  The results showed the predicted dispersion relation from calculated ATR of the surface plasmons polaritons were in good agreement with the dispersion relation from the theory.